Artificial Intelligence, Personal Data, And Digital Surveillance: Uzbekistan’s Constitutional Path to Balance - Shokhjakhon Abudusattorov (International Journal of Law And Criminology, 2025)
This article examines the legal and constitutional challenges posed by the rapid development of artificial intelligence (AI) and mass data processing in Uzbekistan. While the state has introduced a foundational legal framework for personal data protection, it has yet to regulate algorithmic governance, automated decision-making, and digital surveillance mechanisms. The study highlights existing legal gaps, institutional weaknesses, and the need for a rights-based, human-centered approach to digital governance. Comparative analysis with foreign models and a critical look at Uzbekistan’s current trajectory suggest that constitutional adaptation is essential to ensure transparency, accountability, and protection of individual freedoms in the age of AI.